Answer:
x = √17 and x = -√17
Explanation:
We have the equation:
![(3)/(x + 4) - (1)/(x + 3) = (x + 9)/((x^2 + 7x + 12))](https://img.qammunity.org/2022/formulas/mathematics/high-school/8tqghqvclepf63v96t7fw3s1hsvuzdr6uv.png)
To solve this we need to remove the denominators.
Then we can first multiply both sides by (x + 4) to get:
![(3*(x + 4))/(x + 4) - ((x + 4))/(x + 3) = ((x + 9)*(x + 4))/((x^2 + 7x + 12))](https://img.qammunity.org/2022/formulas/mathematics/high-school/lcfy939v4gl79zy12behm5wx1tycbedin7.png)
![3 - ((x + 4))/(x + 3) = ((x + 9)*(x + 4))/((x^2 + 7x + 12))](https://img.qammunity.org/2022/formulas/mathematics/high-school/zep40jtjo17824q0v0gv6tc4es0641k3eo.png)
Now we can multiply both sides by (x + 3)
![3*(x + 3) - ((x + 4)*(x+3))/(x + 3) = ((x + 9)*(x + 4)*(x+3))/((x^2 + 7x + 12))](https://img.qammunity.org/2022/formulas/mathematics/high-school/w6yjufeu2giefy7h0x1e3ou73mechslwoc.png)
![3*(x + 3) - (x + 4) = ((x + 9)*(x + 4)*(x+3))/((x^2 + 7x + 12))](https://img.qammunity.org/2022/formulas/mathematics/high-school/575w0sw4l2rn3q0ayvfo5uzww54mkl45ez.png)
![(2*x + 5) = ((x + 9)*(x + 4)*(x+3))/((x^2 + 7x + 12))](https://img.qammunity.org/2022/formulas/mathematics/high-school/ov4xncoqz052zb5mq0l51r9rmh6sk9wpjb.png)
Now we can multiply both sides by (x^2 + 7*x + 12)
![(2*x + 5)*(x^2 + 7x + 12) = ((x + 9)*(x + 4)*(x+3))/((x^2 + 7x + 12))*(x^2 + 7x + 12)](https://img.qammunity.org/2022/formulas/mathematics/high-school/4bw80zs6wv6o788qvavz0art1wprf0razz.png)
![(2*x + 5)*(x^2 + 7x + 12) = (x + 9)*(x + 4)*(x+3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/2j1wddt7teke7e4l62zirptvh5grcwpva2.png)
Now we need to solve this:
we will get
![2*x^3 + 19*x^2 + 59*x + 60 = (x^2 + 13*x + 3)*(x + 3)](https://img.qammunity.org/2022/formulas/mathematics/high-school/qfhg6a9r09xoo840hwdq12z32lddnvi9e5.png)
![2*x^3 + 19*x^2 + 59*x + 60 = x^3 + 16*x^2 + 42*x + 9](https://img.qammunity.org/2022/formulas/mathematics/high-school/fm45zhzut3h9sv3lu519qoz0yznvff19xl.png)
Then we get:
![2*x^3 + 19*x^2 + 59*x + 60 - ( x^3 + 16*x^2 + 42*x + 9) = 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/qwwhzn56rt3v4izn3pdclj64wphtvrao3e.png)
![x^3 + 3x^2 + 17*x + 51 = 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/2500ak6zh3502oe7wswc56z4weaebsxss2.png)
So now we only need to solve this.
We can see that the constant is 51.
Then one root will be a factor of 51.
The factors of -51 are:
-3 and -17
Let's try -3
p( -3) = (-3)^3 + 3*(-3)^2 + +17*(-3) + 51 = 0
Then x = -3 is one solution of the equation.
But if we look at the original equation, x = -3 will lead to a zero in one denominator, then this solution can be ignored.
This means that we can take a factor (x + 3) out, so we can rewrite our equation as:
![x^3 + 3x^2 + 17*x + 51 = (x + 3)*(x^2 + 17) = 0](https://img.qammunity.org/2022/formulas/mathematics/high-school/bgl2opg6u3w62tj3ltxotspzsjbe4rr7g0.png)
The other two solutions are when the other term is equal to zero.
Then the other two solutions are given by:
x = ±√17
And neither of these have problems in the denominators, so we can conclude that the solutions are:
x = √17 and x = -√17